Neuro-fuzzy current controller for three-level cascade inverter based D-STATCOM - Deniz, Erkan; Tuncer, Servet; Coteli, Resul; Ata, Fikret; Dandil, Besir; Gencoglu, Muhsin T. (My University, 2010)
Distribution STATCOM (D-STATCOM) is a custom power device connected in parallel to power system. In this paper, Neuro-Fuzzy Controller (NFC) which has robust structure is proposed for control of D-STATCOM's dq-axis currents. Designed NFC is first order Mamdani type NFC structure and has two inputs, one output and six layers. D-STATCOM is based on three-level cascaded inverter and this inverter is controlled with Sinusoidal Pulse Width Modulation (SPWM) technique. dSPACE's DS1103 control card is used for real-time implementation of D-STATCOM's control algorithm. The performance of D-STATCOM using NFC is evaluated by changing of reference reactive current (iqref) as on-line. Under this condition, some experimental results obtained from experimental setup are given.
2010 45th International Universities' Power Engineering Conference, UPEC 2010 -- 31 August 2010 through 3 September 2010 -- Cardiff -- 83405
Keywords: D-STATCOM; Neuro-fuzzy current controller; SPWM; Three-level cascade inverter